2023
DOI: 10.15360/1813-9779-2023-2-2304
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Alpha Inhibitor Proteins as a Predictor of Necrotizing Enterocolitis in Newborn Infants

Abstract: Necrotizing enterocolitis is a devastating emergency, multifactorial disease. Inter-alpha inhibitor proteins are serine protease inhibitors involved in many physiological and pathological activities.Aim: this study was designed in order to assess the value of inter-alpha inhibitor proteins in predicting and improving accuracy of diagnosis of NEC in newborn infants with non- precise abdominal and intestinal manifestations.Materials and Methods. This study was prospective longitudinal research that included 80 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…IMA levels increased in the following days in newborns with stage II and stage III NEC, and these increases were higher, especially in children with stage III NEC [34]. Meneza S. et al also showed a positive correlation between serum IMA level and healing time [35].…”
Section: Inflammation/ Intestinal Injurymentioning
confidence: 90%
“…IMA levels increased in the following days in newborns with stage II and stage III NEC, and these increases were higher, especially in children with stage III NEC [34]. Meneza S. et al also showed a positive correlation between serum IMA level and healing time [35].…”
Section: Inflammation/ Intestinal Injurymentioning
confidence: 90%